Use of the CodeIgniter Framework in Developing Online Registration and Pre/PostTest Education and Training Applications at BKA Aceh - Nurul Hamdi; Widya Almaira (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
This study analyses the use of the Codeigniter Framework in developing an online training registration and pre/posttest application at the Aceh Civil Service Agency (BKA). The purpose of this research is to build an information system that can provide general information about training, as well as facilitate registration and pre/posttest online and real-time. This research uses the method of needs analysis and system design analysis. The results of this study indicate that the system developed can provide easy access to prospective participants to find out the training schedule. Admin can access data related to training schedules, participants, and committees, while the committee can manage pre/post test questions and exam results. The system allows participants to access modules and pre/posttests after registering. Exam result data can be used as a reference in decision-making related to job promotions that require training qualifications. In conclusion, the use of the Codeigniter Framework is effective in developing online registration and pre/posttest training applications at BKA Aceh.